(untitled) (Papeles, 2023)
The following work is an approximation and analysis of the social and assistance policies that were implemented in the province of Santiago del Estero between 1946 and 1952, particularly in the area of health, education, and housing. These policies, which are part of the first national Peronist government and have their correlate at the local level, gave an account of the particularities of the social issue in the province and how the changes and transformations that were generated around the modernization of the provincial State, had an impact on social reality and deserved special attention from it. Likewise, an approximation to the State-Social Policy-Social Work trinomial will be carried out.